English Novice Teachers’ Beliefs on Teaching in Inclusive Classroom - Nurkhamidah, Neni; Rizal, Rizka Patrika; Marleni, Sri (STKIP AGAMA HINDU SINGARAJA, 2024)
To achieve educational objectives on inclusive class in Merdeka Curriculum setting, teachers should possess awareness of their personal beliefs. As the ones who play important roles in the classrooms, teachers have to decide what will be needed or what will work best for their students, including in the inclusive classes. Therefore, this qualitative study aims to find out English pre-service teachers' beliefs toward the implementation of inclusive class on Merdeka Curriculum. The data were collected by interviewing five English pre-service teachers who have conducted the inclusive class in their internship program. The results of this study indicated that the novice teachers have various beliefs; 1) concerning on the teachers’ important roles in the inclusive classes that they have to work harder than in general classes; 2) regarding the teachers’ skills to be possessed, they are planning and class management skills; 3) respecting the factors that lead them to be successful in the inclusive classes; and 4) relating to the training that might help them in conducting the inclusive classes.